2022
DOI: 10.3390/ijerph19137786
|View full text |Cite
|
Sign up to set email alerts
|

Experience of Bangladeshi Dental Students towards Online Learning during the COVID-19 Pandemic: A Web-Based Cross-Sectional Study

Abstract: Background: During the COVID-19 pandemic, dental education institutions throughout the world experienced significant challenges, including a quick shift to an online learning paradigm. Since the pandemic has had a considerable impact on dental education, this research evaluated the perspectives and attitudes towards online learning among undergraduate dental students in Bangladesh. Methods: The research was conducted through a cross-sectional method using self-administered online questionnaires. The questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 50 publications
1
16
0
1
Order By: Relevance
“…The dependent variable was level of satisfaction with virtual classes. The independent variables were sex, 14 , 16–18 monthly family income, 20 computer use 21 and age group. 4 , 22 The possible confounding variables were marital status, 2 , 23 academic year, 15 , 17 , 24 area of residence, 17 , 25 place of origin 22 , 26 , 27 and occupation.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dependent variable was level of satisfaction with virtual classes. The independent variables were sex, 14 , 16–18 monthly family income, 20 computer use 21 and age group. 4 , 22 The possible confounding variables were marital status, 2 , 23 academic year, 15 , 17 , 24 area of residence, 17 , 25 place of origin 22 , 26 , 27 and occupation.…”
Section: Methodsmentioning
confidence: 99%
“…For example, with respect to the academic year, Islam et al 14 and Sarialioglu-Gungor et al 15 found that first-year dental students had higher dissatisfaction compared to students in higher years. 14 , 15 On the other hand, Altawel et al and Taher et al reported that being female and being a fourth- and fifth-year student positively influenced satisfaction with virtual classes. 16 , 17 While Çirakoglu et al 18 reported that males were more satisfied with virtual classes than females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theo nghiên cứu của Islam, M. I. và cộng sự (2022) [7], nhận thấy rằng hầu hết các sinh viên nha khoa không hài lòng với việc học trực tuyến và thích các khóa học trong khuôn viên trường hơn là giáo dục trực tuyến. Vì giáo dục nha khoa bao gồm một số thành phần, chẳng hạn như bài giảng/hướng dẫn, tương tác học tập dựa trên vấn đề, học tập dựa trên nghiên cứu, các khóa đào tạo mô phỏng và đào tạo kỹ năng lâm sàng [8], các nghiên cứu đã báo cáo rằng các lớp học trực tuyến không khả thi đối với chuyên gia các khóa học nha khoa.…”
Section: Các Quan đIểm Về Sự Hài Lòng Trong Học Tậpunclassified
“…This allows universities to serve more students without physically requiring their presence. [ 2 ] There are challenges which have to be faced by the universities as well as students due to online education. Particularly, compared to face-to-face education, online learning frequently leads to much higher student turnover.…”
Section: Introductionmentioning
confidence: 99%